Implementasi Strategi dan Metode Problem Solving dalam Pembelajaran Fiqih di Ma Roudlotul Jannah - Imam Anas Hadi; Uswatun Chasanah; Sirojul Baehaqi; Isnaeni Agustina; Muhammad Zulfa (At Turots: Jurnal Pendidikan Islam, 2025)
Fiqh learning has characteristics that require in-depth understanding and application skills to solve various problems in everyday life. This study aims to analyze the implementation of problem solving strategies and methods in fiqh learning at MA Roudlotul Jannah. The focus of the study includes planning, implementation, evaluation, and supporting and inhibiting factors in the implementation of problem solving methods. The study used a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The results of the study indicate that the implementation of problem solving strategies in fiqh learning at MA Roudlotul Jannah is carried out through the following stages: (1) identification of problems relevant to students' lives, (2) analysis of problems based on a fiqh perspective, (3) submission of alternative solutions by referring to sources of Islamic law, (4) evaluation and selection of solutions based on the rules of ushul fiqh, and (5) implementation and reflection. This strategy has been proven to improve students' critical thinking skills, conceptual understanding, and application skills in the field of fiqh. The main challenges in implementation include time constraints, diversity in student ability levels, and the need for continuous teacher professional development. The conclusion of the study confirms that the problem solving method is very relevant and effective for contemporary fiqh learning, with the note that there needs to be adaptation that is appropriate to the madrasah context and student characteristics.